How to Handle Pressure to Act Unethically - Haylon, Lisa S.; Bishop, Carol C.; Boyle, Douglas M.; Hermanson, Dana R. (Management Accounting Quarterly, 2022)
It is likely that accountants will face pressure to act unethically during their careers. We offer 10 practical steps to help financial professionals prepare for and respond to the pressure to act unethically.
Keywords: Accounting; Business And Economics--Accounting; Business And Economics--Management; Business ethics; Compliance; Conformity; Decision making; Fraud; Management accountants; Personality; Professionals; dept.acc; peer-reviewed; ⛔ No DOI found

Accounting Program Leaders’ Perceptions of Criteria for Hiring Assistant Professors - Boyle, Douglas M.; Haylon, Lisa S.; Hermanson, Dana R.; Krull, George W., Jr. (Issues in Accounting Education, 2023)
The academic accounting labor market is experiencing rapid changes on several fronts. We examine accounting program leaders’ perceptions of Assistant Professor hiring criteria, including how the criteria have changed in recent years. We ask program leaders to provide qualitative perspectives, rate the importance of 56 possible hiring criteria, and, in a supplemental analysis, rank and rate four hypothetical Assistant Professor candidates. Based on responses from 54 accounting program leaders, the results reveal a complex setting with research and teaching considerations, a focus on collegiality and professional experience, and an increasing focus on diversity. Specifically, Research Intensive schools (Carnegie R1 and/or doctorate in business) are more top-tier research and top-tier doctoral program focused, while Non-Research Intensive schools (all others) are more focused on general skills, other refereed journals, practitioner research, teaching experience, service, CPA licensure, and other professional certifications.
Keywords: dept.acc; peer-reviewed